News from the pit: Journalistic performativity and discourse on Belgian internment policy. (March 2019) - Reul, Robin; Paulussen, Steve; Maeseele, Pieter
Abstract: This contribution examines the ways in which newspapers open or close mediated debate on the Belgian internment issue, and whether this can be connected to different journalistic practices. Although human rights guarantees are often articulated as a matter of near-universal consensus, Belgium has been convicted 23 times by the European Court for Human Rights for its treatment of mentally disabled criminal offenders. Considering news media's central role in shaping debate on human rights issues, we study internment news in two Dutch-language newspapers between 2013 and 2015 using critical discourse analysis. Our research shows that studying media as a site of struggle enables a deeper understanding of how debate is opened or closed, and explores the possibilities of studying discursive strategies that shape the mediated debate together with practices that reinforce journalistic credibility.